1987
DOI: 10.1071/pp9870463
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Partitioning in Leaves of Salt-Stressed Sorghum, Maize, Wheat and Barley

Abstract: Chloride distribution in the blade, sheath and midrib of leaves was determined for several grasses in salinised field plots and in nutrient solutions at various NaCl levels in the greenhouse. Chloride preferentially accumulated in the sheaths relative to the blades in all grass species and varieties examined when Cl- concentrations were expressed on a dry weight basis, although to varying degrees. Substantial levels of Cl- sheath partitioning were obtained only for sorghum when Cl- con- centrations were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
3
5

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 0 publications
4
31
3
5
Order By: Relevance
“…12, 19 and 25 days old) in comparison with control plants in our study. High tissue Na + and Cl -in shoots of common bean is consistent with observations (Boursier et al 1987) that salt-sensitive plants generally have a poor capacity to restrict accumulation of these ions in shoots. Our study showed that plant hypocotyls generally had higher Na + concentration than shoots at tested plant ages of 12, 19 and 25 days.…”
Section: Discussionsupporting
confidence: 74%
“…12, 19 and 25 days old) in comparison with control plants in our study. High tissue Na + and Cl -in shoots of common bean is consistent with observations (Boursier et al 1987) that salt-sensitive plants generally have a poor capacity to restrict accumulation of these ions in shoots. Our study showed that plant hypocotyls generally had higher Na + concentration than shoots at tested plant ages of 12, 19 and 25 days.…”
Section: Discussionsupporting
confidence: 74%
“…Portanto, os mecanismos que resultam no excesso de absorção iônica e exclusão de Na + e Cl -de tecidos metabolicamente ativos da parte aérea das plantas, podem ser responsáveis pela tolerância das culturas ao estresse salino (Cheeseman, 1988). Esta exclusão pode ser efetuada por acumulação preferencial de íons em tecidos, relativamente, tolerantes da raiz ou da parte aérea (Boursier et al, 1987).…”
Section: Introductionunclassified
“…Os íons inorgânicos desempenham importante papel na preservação do potencial hídrico vegetal; portanto, mecanismos em plantas que levam ao excesso de absorção iônica e exclusão de Na + e Cl -de tecidos metabolicamente ativos da parte aérea podem ser responsáveis pela tolerância das culturas ao estresse salino (Greenway & Munns, 1980). Essa exclusão pode ser efetuada pela acumulação preferencial de íons em tecidos relativamente tolerantes da raiz ou da parte aérea (Boursier et al, 1987).…”
Section: Introductionunclassified